Chemical and Sensory Effects of Cofermentation and Blending of Malbec and Merlot Wines from the Central Coast of California - L. Federico Casassa; Armando Vega-Osorno; Anibal A. Catania; James F. Harbertson (Australian Journal of Grape and Wine Research)
Background and Aims. Cofermentation and blending are traditional winemaking practices. This study reports their comparative chemical and sensory outcomes. Methods and Results. Malbec and Merlot were made into monovarietal wines, cofermented (COF), blended postalcoholic (PAF), and postmalolactic fermentation (PMLF), at a 50/50 proportion. Wines were followed up to 3 years of bottle aging. Tannins were 50% higher in monovarietal Merlot wines, which improved production of large polymeric pigments in Merlot-based cofermented and blended wines. Addition of Malbec favored production of small polymeric pigments. After 3 years of bottle aging, polymeric pigments were higher in cofermented and blended wines. PMLF blended wines showed 15% improved copigmentation and 25% increase in wine colour. The perception of wine length was positively correlated with red fruit aroma (R2 = 0.94 and p=0.006) and negatively correlated with earthy aroma (R2 = 0.91 and p=0.012). Conclusions. Blending postalcoholic fermentation highlighted more of the individual character of each monovarietal wine in the final blend. Cofermentation and postmalolactic fermentation blending tended to equalize the sensory profile of the resulting wines but also showed higher complexity of aromas than monovarietal wines. Significance of the Study. Cofermentation and blending are both suitable winemaking practices for increasing the polymeric pigment content and the sensory complexity of the resulting wines.